Neuroprotective effect of echinoside on MPTP-induced Parkinson's disease mouse model by activation of NRF2/HO-1 pathway - Zimeng Li; Hongyan Li (Pharmacological Research - Modern Chinese Medicine)
Echinacoside, a principal active compound derived from Cistanche deserticola Ma, is recognized in traditional Chinese medicine for its anti-aging, immunomodulatory, endocrine-regulating, and neuroprotective properties. However, the specific neuroprotective mechanisms of echinacoside remain largely unclear. This study aims to investigate whether the neuroprotective effects of echinacoside in a mouse model of Parkinson's disease (PD) are mediated through the Nrf2/HO-1 signaling pathway by mitigating inflammatory responses. Mice were divided into four groups: control, model, positive control, and echinacoside-treated groups. PD mouse model was induced through intraperitoneal injection of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) over the course of one week, followed by three weeks of oral administration of echinacoside. The results demonstrated that echinacoside significantly improved motor function impairments caused by MPTP in PD mice. Immunohistochemical analysis revealed that echinacoside enhanced the expression of tyrosine hydroxylase in the substantia nigra of PD mice. Furthermore, assays of inflammatory cytokines indicated that echinacoside effectively reduced the levels of IL-6 and TNF-α in brain tissues. Western blot analysis further confirmed that echinacoside intervention upregulated the expression of Nrf2 and HO-1 in the brain tissues of PD mice. These findings suggest that echinacoside exerts neuroprotective effects in the PD mouse model, likely through the activation of the Nrf2/HO-1 signaling pathway. Therefore, echinacoside may be considered a potential therapeutic strategy for the treatment of PD.